Banach-Mackey spaces - Jing Hui Qiu; Kelly McKennon (International Journal of Mathematics and Mathematical Sciences)
In recent publications the concepts of fast completeness and local barreledness have been shown to be related to the property of all weak-* bounded subsets of the dual (of a locally convex space) being strongly bounded. In this paper we clarify those relationships, as well as giving several different characterizations of this property.